Carbonated and chloride contaminated concrete structure: the role of molybdenum in corrosion of stainless steel reinforcement - Araujo,A. (2013)
This paper is a contribution to the understanding of the role of molybdenum (Mo) in the pitting corrosion resistance of stainless steels in concrete contaminated with chloride ions after its carbonation. For the study, samples of ferritic, austenitic and duplex stainless steels were produced in laboratory with controlled levels of molybdenum (Mo). Samples of theses steels were immersed in simulated carbonated and noncarbonated concrete pore solutions, both with the addition of 3.5 % of NaCl. Other samples were embedded in concrete that was later carbonated and immersed in NaCl solution. The performance of the steels in concrete was verified through corrosion potential monitoring (several months) followed by electrochemical experiments (anodic polarization). Finally, the optical and electronic microscopy techniques were used to analyze the corrosion attacked surfaces.